Promotion of Instagram and Purchase Intention: A Case of Beverage Business at Covid-19 Pandemic - Habibie, Fachrul Husain; Mustika, Amalia; Ratnaningtyas, Heny; Noveti, Velicia (Jurnal Penelitian Pariwisata, 2021)
This study aims to analyze the effect of Instagram promotion on buying interest at Yogo Living World. This study uses a descriptive correlational method with a quantitative approach. The unit of analysis in this study is Yogo Living World consumers with a sample size of 100 individuals using probability sampling techniques. This study uses a simple linear regression test. The results of the descriptive statistical test show that: (1) Instagram promotion is in the fairly interesting category with an average score of 3.81 and (2) purchase intention is in the fairly interesting category with an average score of 3.87. The coefficient of determination test results show that the promotion factor of Instagram has an effect of 74.1% on buying interest at Yogo Living World and the remaining 25.9% is influenced by other factors that are not examined. The t test shows that Instagram promotion has a significant effect on buying interest at Yogo Living World. The culinary business is promoted through social media, especially Instagram, which can describe product profiles ranging from taste, appearance and service through videos displayed on social media. In Instagram promotions, the hashtag indicator adds hashtag variations, the number of hashtags, and provides special promotions for customers who use hashtags. Keywords: Promotion of Instagram, Purchase Intention, Yogo Living World